Pengaruh Modulasi M-PSK Pada Unjuk Kerja Sistem Orthogonal Frequency Division Multiplexing (OFDM) - Ajub Ajulian Zahra; Imam Santoso; Wike Septi Fadhila (Transmisi: Jurnal Ilmiah Teknik Elektro, 2012)
OFDM (Orthogonal Frequency Division Multiplexing) is a transmission technique which uses some orthogonal subcarrier frequencies (multicarrier). Each of the subcarrier is modulated by conventional modulation technique at low symbol ratio. It can be a PSK (Phase Shift Keying) modulation. PSK modulation is chosen as its simplicity and ability to reduce amplitude fluctuation which could leads to attenuation.A simulation with Matlab is made in this final project. The purpose of this simulations is to analyze M-PSK modulation effect on OFDM system performance under AWGN (Additive White Gaussian Noise)  noisy channel condition. System parameter that being changed is modulation level of PSK with system inputs consist of random data, grayscale images, and sounds. OFDM system performance is observed by analyzing Bit Error Rate (BER) values and Signal to Noise Ratio (SNR) received by OFDM receiver by varying channel SNR value.The results show that in grayscale pictures and sounds transmission, BPSK is the most noise  durable modulation technique compared with QPSK, 16PSK, and 256PSK. It can be shown from the least BPSK BER value compared with other three modulations. Received SNR value shows received image quality on receiver side. The simulation results show that on high noise channel condition (channel SNR <6dB) using 256PSK is better than BPSK, QPSK or 16PSK.Keywords: OFDM, PSK, BER, SNR